A note on lower bounds for maximum genus - Chen, Yichao; Liu, Yanpei (Utilitas Mathematica, 2007)
In this paper, the lower bounds for maximum genus of a graph which does not contain three special structures are obtained, which improve a lower bound of maximum genus [1] for non-simple graphs in some sense.